DNA methylation signatures to predict the cervicovaginal microbiome status - Nené, Nuno R; Barrett, James; Jones, Allison; Evans, Iona; Reisel, Daniel; Timms, John F; Paprotka, Tobias; Leimbach, Andreas; Franchi, Dorella; Colombo, Nicoletta; Bjørge, Line; Zikan, Michal; et al. (Clinical epigenetics, 2020)
BACKGROUND: The composition of the microbiome plays an important role in human health and disease. Whether there is a direct association between the cervicovaginal microbiome and the host's epigenome is largely unexplored. RESULTS: Here we analyzed a total of 448 cervicovaginal smear samples and studied both the DNA methylome of the host and the microbiome using the Illumina EPIC array and next-generation sequencing, respectively. We found that those CpGs that are hypo-methylated in samples with non-lactobacilli (O-type) dominating communities are strongly associated with gastrointestinal differentiation and that a signature consisting of 819 CpGs was able to discriminate lactobacilli-dominating (L-type) from O-type samples with an area under the receiver operator characteristic curve (AUC) of 0.84 (95% CI = 0.77-0.90) in an independent validation set. The performance found in samples with more than 50% epithelial cells was further improved (AUC 0.87) and in women younger than 50 years of age was even higher (AUC 0.91). In a subset of 96 women, the buccal but not the blood cell DNA showed the same trend as the cervicovaginal samples in discriminating women with L- from O-type cervicovaginal communities. CONCLUSIONS: These findings strongly support the view that the epithelial epigenome plays an essential role in hosting specific microbial communities.
Keywords: DNA Methylation; epitelové buňky; Epigenome; metylace DNA; High-Throughput Nucleotide Sequencing; mikrobiota; Lactobacillus; Epithelial Cells; CpG ostrůvky; Adult; dospělí; Microbiota; lidé; ženské pohlaví; Humans; cervix uteri; vysoce účinné nukleotidové sekvenování; epigenom; prediktivní hodnota testů; CpG Islands; Female; Vagina; vagina; lidé středního věku; Predictive Value of Tests; Cervix Uteri; Middle Aged